Topical Timolol 0.5% Gel‐Forming Solution for Small Deep Facial Infantile Hemangiomas. Issue 5 (26th July 2013) - Sorrell, Jennifer; Chamlin, Sarah L.
Abstract We report three cases of successful treatment of proliferating deep infantile hemangiomas with topical timolol 0.5% gel‐forming solution (GFS) used two to three times daily. We recommend considering timolol as an initial option for small, deep facial hemangiomas that are not causing functional compromise or complications but may have an unsatisfactory cosmetic appearance. In our experience, albeit limited, this is a safe alternative to watchful waiting.